2009
DOI: 10.2319/082408-448.1
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Anomalies and Normal Variants in Patients with Palatally Displaced Canines

Abstract: Objective: To test the null hypothesis that there is no increased prevalence of skeletal anomalies and/or normal variants as evidenced by the cephalometric radiographs of patients with palatally displaced canines (PDC). Materials and Methods:The treatment records of 38 white subjects between 14 and 20 years old with PDC were collected and evaluated retrospectively. Inclusion criteria for the study required that the case records include good-quality panoramic radiographs and lateral cephalometric radiographs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 25 publications
5
48
2
4
Order By: Relevance
“…This study found a higher percentage of males with PP but there is no consensus regarding the prevalence of PP in males compared with females (Geist et al). The frequency of PP increased in subjects with palatally displaced canines in accordance with Leonardi et al (2009). It may act as a useful diagnostic predictor of susceptibility to local dental problems.…”
Section: Discussionmentioning
confidence: 84%
“…This study found a higher percentage of males with PP but there is no consensus regarding the prevalence of PP in males compared with females (Geist et al). The frequency of PP increased in subjects with palatally displaced canines in accordance with Leonardi et al (2009). It may act as a useful diagnostic predictor of susceptibility to local dental problems.…”
Section: Discussionmentioning
confidence: 84%
“…A dentist on the alert may suspect a new case of Gardner syndrome by observing atypical osteoma-like lesions in a young patient and referring him/her to medical evaluation 10 . Palatally impacted maxillary canines seem to have a genetic etiology 6,11 , and are frequently associated with other changes, such as microdontia of maxillary lateral incisors [11][12] , delayed tooth eruption 13 and fusion of the clinoid processes of the sella turcica 14 . Idiopathic osteosclerosis is a bone tissue structural change whose etiologic factor remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, the cervical vertebrae are not given due attention during routine orthodontic evaluation of lateral cephalograms. Studies have shown that various cervical vertebral anomalies and pathologies can be detected in lateral cephalograms [25]. One of such anomalies that can be discerned by watchful eyes is ponticulus posticus.…”
Section: Introductionmentioning
confidence: 99%